2022
DOI: 10.1093/burnst/tkac015
|View full text |Cite
|
Sign up to set email alerts
|

Control of fibrosis and hypertrophic scar formation via glycolysis regulation with IR780

Abstract: Background Hypertrophic scars (HS) represent one of the most common clinical challenges due to unsatisfactory therapeutic results. HS formation is associated with the abnormal activation of fibroblasts and their excessive fibrotic behavior. Glycolysis dysregulation has been shown to participate in the incidence and progression of various fibrotic diseases and shows potential as a means of controlling HS formation. This work aimed to discuss the impact of augmented glycolysis on HS and to prop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 28 publications
(33 reference statements)
0
2
0
Order By: Relevance
“…After regional injection of miR-203a-3p, the scar appearance was noticeably improved, while the cross-sectional area, scar elevation index, collagen density and scar index were significantly decreased, indicating that miR-203a-3p improved the morphology and histological phenotypes of scars in vivo [ 47 ]. Previous studies have shown that α-SMA is highly expressed in fibrotic disease-derived myofibroblasts [ 48 , 49 ]. Our IHC results also showed a significant reduction in α-SMA in miR-203a-3p-treated scars, suggesting that miR-203a-3p inhibited fibroblasts transdifferentiation in vivo .…”
Section: Discussionmentioning
confidence: 99%
“…After regional injection of miR-203a-3p, the scar appearance was noticeably improved, while the cross-sectional area, scar elevation index, collagen density and scar index were significantly decreased, indicating that miR-203a-3p improved the morphology and histological phenotypes of scars in vivo [ 47 ]. Previous studies have shown that α-SMA is highly expressed in fibrotic disease-derived myofibroblasts [ 48 , 49 ]. Our IHC results also showed a significant reduction in α-SMA in miR-203a-3p-treated scars, suggesting that miR-203a-3p inhibited fibroblasts transdifferentiation in vivo .…”
Section: Discussionmentioning
confidence: 99%
“…The levels of Kla were found to be significantly lower in hypertrophic scar tissues and fibroblasts than in normal skin tissues and fibroblasts. However, previous reports have indicated the presence of augmented glycolysis and lactate accumulation in hypertrophic scar fibroblasts (HSF) and hypertrophic scar (HS) tissues . This discrepancy may be attributed to variations in the samples used.…”
Section: Discussionmentioning
confidence: 99%
“…Augmented glycolysis has been confirmed in HS and is essential for the excessive fibrotic behavior exhibited by HS fibroblasts . In this study, we identified numerous lactylation sites on enzymes involved in glycolysis/gluconeogenesis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the epigenetic machinery, strategies that target the imbalanced metabolic pathways in both RA SFs and CAFs have been employed to reduce RA severity and inhibit tumour growth respectively (158,159)). Interestingly, a recent study proposes a new strategy to control fibrosis and hypertrophic scars formation using an anti-glycolytic agent that regulates fibroblasts activity (160). Glycolysis inhibition has also been shown to reduce cardiac fibroblasts activation in-vitro and to control cardiac fibrosis in mice with myocardial infarction (69).…”
Section: Therapeutic Perspectives Of Targeting Fibroblasts In Inflamm...mentioning
confidence: 99%